Application Of The Value Engineering Concept On Building Construction Projects In Malinau Regency In Facing The Covid-19 Pandemic - Theofilus Yoel Lufung; Novi Andhi Setyo Purwono; Ilham Poernomo; Emeliano Maria Gusmão de Oliveira (Eduvest - Journal of Universal Studies, 2022)
This study uses data in the form of planning and implementation data for the construction of the Malinau District Arts Building. Data development is carried out by conducting Value Engineering analysis starting from the project information collection stage, followed by function analysis using the Law of Pareto. The method used to analyze the function is F.A.S.T diagram (Function Analysis System Technique) and Cost to Worth. Followed by the creativity stage to come up with new alternative designs that can minimize project costs. The selected design will be evaluated at the evaluation stage, then the development stage will be carried out to obtain cost savings on the type of work that has been analyzed by VE in detail. From the data analysis at the planning stage, the savings reached Rp. 642,220,790, while in the construction phase, savings of Rp. 491,286,382, in 80% of the jobs with the highest cost items.